Personal characteristics of the young people in a difficult life situation - Ignatova, Ekaterina S.; Suslova, Elena D.; Bazueva, Angelica A. (Opción, 2019)
The article is aimed at investigating the personal characteristics of the young people who face a difficult life situation. Buss-Durkee questionnaire, Taylor Manifest Anxiety Scale and the techniques of detecting the levels of subjective feelings of loneliness of D. Russell and M. Ferguson are applied in this research. As a result, the persons with disabilities manifest comparatively higher levels of aggressiveness, anxiety and loneliness than healthy people. As a conclusion, the idea of the dialogicality of society, provides a possibility to form a constructive interaction experience in communication. Its effectiveness increases through the use of the integrative approach